Ivabradine In Patients With Systemic Inflammatory Response Syndrome (Journal of Pharmaceutical Negative Results, 2023)
Introduction: ivabraddine is a pure heart rate lowering medication that its usage is beneficial in SIRS and MODS as it can reduce heart rate and decrease oxygen consumption especially at low ejection fraction where other medications cannot undergo their potential cardioprotective effect. Aim of work: The aim of this case study was to report the use of Ivabradine in patients who developed SIRS and compare this group with patients who developed SIRS without Ivabradine use for incidence of changes in systolic and diastolic indices, ejection fraction EF and cardiac index CI and effects on hemodynamics, organ perfusion parameters, and outcome of SIRS and MODS. Patients and methods: Patients who presented to emergency department with SIRS and admitted to ICU. The study population will include 40 patients who developed SIRS and admitted to ICU. A total of 40 patients were divided into two groups: Group I: SIRS patients with ivabradine treatment. Group II: SIRS patients without Ivabradine treatment. Results; Comparative study between the 2 groups revealed, highly significant increase in follow up SvO2, EF and CI, at end of Ivabradine treatment, compared to control group without Ivabradine treatment (p < 0.05 respectively). Conclusion: By comparative study between two groups of sepsis there was a significant improvement in cardiac indices in Ivabradine group at the end of the study (high cardiac index and ejection fraction), In addition to improvement of petfusion parameters.